(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article delves into the pedagogical significance of role-playing activities as an effective method to enhance negotiation skills in English as a Second Language (ESL) learners. In the modern era of globalization, where English serves as the lingua franca of international business, education, and diplomacy, the ability to negotiate effectively in English is an invaluable skill. The article outlines the theoretical foundations of role-playing, explores its integration into communicative language teaching methodologies, and offers detailed examples of classroom practices that promote strategic linguistic competence.